Development Of a Peer Empowerment Program Model For Improving Adolescent Healthy Lifestyle Motivation in Hinterland Areas - Septi Maisyaroh Ulina Panggabean; Netty Herawaty Purba; Aufa Nabilla (International Journal of Health and Medicine, 2025)
A healthy lifestyle is an important issue that needs to be instilled early in life, especially during adolescence. Adolescents living in hinterland areas often face greater challenges in accessing adequate health information and facilities. Therefore, efforts to promote healthy lifestyles among adolescents, especially in hinterland areas, are very important to prevent health problems and improve quality of life. One potentially effective approach to improve the motivation and healthy lifestyle behavior of adolescents in hinterland areas is the Peer Empowerment program. This program utilizes the strong influence of peers in motivating and encouraging positive behavior change among adolescents. This research will use the research and development (R&D) method with an experimental approach. The results of this study are useful for providing recommendations for effective health promotion methods for healthy lifestyle changes in adolescents.